Evaluation Of Higher Moment Capital Asset Pricing Model And Stock Market Technical Efficiency With Stochastic Frontier Approach - Hasan, Md. Zobaer (2014)
The Capital Asset Pricing Model (CAPM) is a revolutionary input in financial theories. It postulates an equilibrium linear relationship between expected return and risk of an asset. The theoretical validity of CAPM is well-tested and accepted but the practical validity of CAPM is still in question. Several studies on CAPM and higher moment CAPM (H-CAPM) have been conducted in Western countries. However, only a few studies have been conducted on the Dhaka Stock Exchange (DSE) market of Bangladesh, which is based on CAPM but not H-CAPM. According to Standard and Poor’s Emerging Stock Markets Fact Book 2000, the DSE is a frontier emerging market in South Asia. To date, no studies have measured the technical efficiencies of companies listed in the DSE market using risk factors derived from H-CAPM. Therefore, this study began with a validity test of the CAPM for individual companies and their constructed portfolios of the DSE market. Based on the present investigation, the standard form of CAPM or mean-variance CAPM was rejected in both cases (individual companies and portfolios) of the DSE market. That is why, to search for an alternative model to explain the risk-return relationship of risky assets, the mean-variance CAPM was extended by taking higher moments: skewness and kurtosis. The results showed that the coefficient of determination increased after inclusion of the higher moments. And, the expected rate of return was related to the coskewness and cokurtosis, but not to the systematic variance or beta. Therefore, the H-CAPM is superior to the mean-variance CAPM in explaining the risk-return relationship in the context of DSE market.